2012
DOI: 10.1182/blood-2012-02-410076
|View full text |Cite
|
Sign up to set email alerts
|

Semaphorin 6A regulates angiogenesis by modulating VEGF signaling

Abstract: Formation of new vessels during development and in the mature mammal generally proceeds through angiogenesis. Although a variety of molecules and signaling pathways are known to underlie endothelial cell sprouting and remodeling during angiogenesis, many aspects of this complex process remain unexplained. Here we show that the transmembrane semaphorin6A (Sema6A) is expressed in endothelial cells, and regulates endothelial cell survival and growth by modulating the expression and signaling of VEGFR2, which is k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
89
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(95 citation statements)
references
References 51 publications
(92 reference statements)
4
89
0
2
Order By: Relevance
“…Although semaphorins were originally thought to mediate axon guidance during the development of central nervous system, 42 a number of the family members such as SEMA3A, SEMA3E, SEMA3F, SEMA4D, and SEMA6A are expressed in EC and play various roles in endothelium. [43][44][45] In particular, SEMA3E 30,43 and SEMA6A 45 have been implicated in regulating vascular patterning and EC repulsion, and this is supported by our data.…”
Section: S259asupporting
confidence: 88%
“…Although semaphorins were originally thought to mediate axon guidance during the development of central nervous system, 42 a number of the family members such as SEMA3A, SEMA3E, SEMA3F, SEMA4D, and SEMA6A are expressed in EC and play various roles in endothelium. [43][44][45] In particular, SEMA3E 30,43 and SEMA6A 45 have been implicated in regulating vascular patterning and EC repulsion, and this is supported by our data.…”
Section: S259asupporting
confidence: 88%
“…Two studies investigating Sema6A in the context of endothelial cells demonstrated contrasting effects of this molecule on angiogenesis. One study demonstrated a proangiogenic effect of Sema6A in the setting of retinal vascular development and found that endothelial cell expression of Sema6A promoted EC survival, VEGFR2 expression, and responsiveness to VEGF (38). A second study of endothelial cells demonstrated that Sema6A can exert an antiangiogenic effect.…”
Section: Discussionmentioning
confidence: 99%
“…Such semaphorins are therefore considered as targets for the development of novel cancer therapeutics. Interestingly, some semaphorins such as sema3C, sema6A and sema3E display dual activities and have been characterized in some publications as inducers of tumor progression 108,[111][112][113][114] and in other publications as inhibitors of tumor progression. 61,92,115,116 The mechanisms responsible for this duality are not yet completely clear and are likely the result of post translational processing and the formation of complex associations between semaphorin receptors and other types of membrane bound receptors such as various tyrosinekinase receptors and adhesion receptors.…”
Section: Semaphorins As Regulators Of Tumor Progressionmentioning
confidence: 99%
“…255 However, sema6A may also be required for the survival of endothelial cells. Silencing its expression in endothelial cells leads to apoptosis and in-vivo to reduced tumor angiogenesis and tumor development due to inhibition of VEGF induced VEGFR-2 mediated signal transduction which can be rescued by the addition of the exogenous soluble extracellular domain of sema6A, 108 suggesting that it can affect tumor angiogenesis and tumor progression utilizing diverse mechanisms of action. In addition, inhibition of sema6A expression as well as MICAL-1 expression in melanoma cells containing mutated B-RAF inhibited tumor progression while overexpression of sema6A in these cells promoted tumor progression, 256 suggesting that the effects of sema6A on tumor progression may vary depending on tumor type.…”
mentioning
confidence: 99%